Hubungan antara Kadar LDL dan HDL terhadap Kejadian Kaki Diabetik pada Pasien DM Tipe 2 di Poli Interna RSD dr. Soebandi: Penelitian Case Control (Relationship between LDL and HDL Levels and Diabetic Foot Incidende in DM Type 2 Patients at the Internal M - Nadia Putri Yurianto; Ali Santoso; Al Munawir (Pustaka Kesehatan, 2017)
Diabetic foot is a complication of type 2 DM that happen because of atherosclerosis, which one of the risk factor is dyslipidemia. The LDL and HDL are the indicator of dyslipidemia. The purpose of this study was to investigate the relationship between LDL, HDL and ratio of LDL/HDL levels on diabetic foot complication of type 2 DM patients at the dr. Soebandi hospital. This was a case control study. The total sample was 61 patients. The result showed that there were no correlation between LDL levels and diabetic foot (p = 0,59) as well as the LDL / HDL ratio (p = 0,5). There was no correlation between HDL and diabetic foot (p = 0.063), but they had a clinical relationship because there were over 20% proportion differences. The OR value between HDL levels and diabetic foot was 6.75. In conclusion, there were no relationship between LDL levels and ratio of LDL/HDL on diabetic foot, but there is clinical relationship between HDL levels on diabetic foot. Keywords: diabetic foot, type 2 DM, LDL, HDL, ratio of LDL/HDL